Crime in the Kingdom: The Effects of Low Self-Control in a Saudi Arabian Sample of Youth. (July 2016) - Sacarellos, Catherine Dimos; Wright, John Paul; Almosaed, Nora F.; Moghrabi, Sameera S.; Bashatah, Fawzia S.; Morgan, Mark Alden
Low self-control has emerged as a ubiquitous predictor of a range of behaviors and life outcomes, including criminal and analogous behaviors. Evidence linking self-control to criminal conduct, moreover, has also emerged from several cross-cultural studies. While important, cross-cultural studies remain limited in number and in scope. Extending empirical investigations into the effects of self-control cross-culturally, we present findings from data collected from Saudi Arabian high school youth. Low self-control was a substantive predictor of self-reported delinquency, violent behavior (VB), victimization, and delinquent peer associations for males and females. The effects of low self-control were found to be substantive, general, and invariant across sex within a culture that practices sex segregation and one that embraces harsh punishments for violent conduct.